(untitled) (Academia Science Repository, 2023)
Vocabulary is one of the key elements of language proficiency. The more words a person knows, the more accurately and diversely he can express his thoughts. To better understand the speech of native speakers, to read and write without using a dictionary, you need to figure out how to replenish the vocabulary of English words. It is important to note that expanding your personal vocabulary is an ongoing process that requires constant practice.